Sectoral specifities in the dynamics of US manufacturing firms - Giulio Bottazzi; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
The size distribution and growth rates dynamics of U.S. manufacturing firms have been extensively studied by many authors. In this paper, using the COMPUSTAT database, we extend the analysis to disaggregated data, studying 15 industrial sectors. We find that among the stylized facts presented in literature concerning the whole industry, some survive and can be considered valid for each single sector while some disappear, suggesting that their emergence was purely due to aggregation effects. The degree of heterogeneity in the behavior of the different sectors hints at a richer economic structure and, consequently, stresses the loss of information implied in limiting the investigations at an aggregate level.
Keywords: 330; Firm Growth; Laplace distribution; Power Law; Industrial Sectors; Unternehmenswachstum; Industrie; Betriebsgrößenstruktur; Branche; USA